New frontiers in reproductive immunology research: bringing bedside problems to the bench. (September 2011) - Joukhadar, Jennifer; Nevers, Tania; Kalkunte, Satyan
The 31st Annual Meeting of the American Society for Reproductive Immunology provided an excellent platform for basic and clinical scientists to brainstorm on current reproductive health issues such as repeated implantation and pregnancy failure, preterm birth, preeclampsia and genital tract infections such as HIV. The goal of the meeting was to foster cross-pollination of ideas as well as to encourage participation of young investigators in the field. The conference was preceded by the 4th Annual Post-Graduate Workshop with the theme of bringing bedside problems to the bench and facilitating collaboration between clinicians and basic scientists. Christopher Davies and Richard Bronson chaired the conference, which hosted approximately 180 delegates representing more than 26 countries across Asia, Australia, Latin America, Europe and North America.